Напрямки подолання наслідків впливу пандемії COVID-19 на м’які навички кадрового потенціалу України - Весоловська, М. К.; Vesolovska, M. K. (Видавництво Львівської політехніки, 2024)
У статті досліджено вплив пандемії COVID-19 на професійні навички української робочої сили. На прикладі Львівської області показано вплив пандемії на стан пра- цездатного населення країни та нові умови для роботи кадрового потенціалу. Проана- лізовано кореляцію між різними факторами, що впливають на розвиток м’яких нави- чок. На основі цього запропонованo напрями подолання наслідків пандемії; побудовано комплексну модель, що узагальнює ці поради та формує розуміння того, як саме вони мають бути застосовані. Дослідження стане корисним для вивчення як м’яких навичок як таких, так і розуміння можливостей їхнього відновлення після наслідків COVID-19; крім того, воно дає змогу краще зрозуміти вплив пандемії на розвиток України загалом.

The purpose of the work is to develop a single comprehensive system that will helpto overcome the consequences of the COVID-19 pandemic impact on the soft skills of the personnel potential of Ukraine. In order to determine the main methods of overcoming the COVID-19 pandemic consequences, a survey of random respondents was conducted. In addition, the purpose of the survey was to assess respondents’ own soft skills during the pandemic and their changes before and after it. The article used the historical method, methods of abstraction, forecasting and analysis. The method of systematization became one of the main ones in achieving the goals and objectives of the research. Thus, we were able to systematize the research results, assess the possibilities for developing a mechanism for overcoming the consequences of the COVID-19 crisis, and form them in a single system. It has been established that the COVID-19 pandemic has a direct impact on the soft skills of personnel potential in Ukraine. People learned how to adapt to new working conditions, how to communicate in an unfamiliar mode, thereby acquiring new skills. The concepts of self-motivation, stability, and adaptability have become more important. The survey conducted in this study confirmed the importance of all these components. The authors of the article propose several strategies for coping with the consequences of the pandemic. The first is independent continuous development and improvement of skills. It can be online training, participation in events, etc. It is also important to provide employees with online tools for collaboration so that employees feel comfortable using the latest technologies. Providing employees with flexible working conditions is also an important aspect, as this will allow them to learn and develop more willingly and effectively. A favorable working environment will help maintain psychological health. Employers can offer employee assistance programs, counseling services, and more. These approaches can significantly increase the effectiveness of the functioning of employees and improve the development of soft skills in the conditions of any crisis. The research is valuable for economic science and has practical significance. The article reveals an understanding of how the COVID-19 pandemic has affected the soft skills of employees, their ability to solve problems, make decisions, communicate, etc. This is how we can formulate people’s ideas about how to improve their skills, how to learn to solve problems that arose during the pandemic. An effective mechanism for overcoming the consequences of the pandemic on the soft skills of human resources (both private and public sectors) is becoming an urgent task for companies, government structures and educational institutions, and therefore important for analysis and research in academic circles. The research is very relevant in modern conditions, as the ability to overcome a crisis is important not only during a pandemic, but also in connection with other factors, in particular, with the beginning of a war and its impact on people’s lives.
A system for overcoming the COVID-19 pandemic effects on the soft skills of human resources
Keywords: робоче середовище; пандемія COVID-19; статистичний аналіз; Софт скілз; віддалена робота; державна політика; work environment; COVID-19 pandemic; statistical analysis; soft skills; remote work; public policy; 658.3.07